Nonnative Proteins Induce Expression of the Bacillus subtilis CIRCE Regulon - Mogk, Axel (American Society for Microbiology (ASM), 1998)
The chaperone-encoding groESL and dnaK operons constitute the CIRCE regulon of Bacillus subtilis. Both operons are under negative control of the repressor protein HrcA, which interacts with the CIRCE operator and whose activity is modulated by the GroESL chaperone machine. In this report, we demonstrate that induction of the CIRCE regulon can also be accomplished by ethanol stress and puromycin. Introduction of the hrcA gene and a transcriptional fusion under the control of the CIRCE operator into Escherichia coli allowed induction of this fusion by heat shock, ethanol stress, and overproduction of GroESL substrates. The expression level of this hrcA-bgaB fusion inversely correlated with the amount of GroE machinery present in the cells. Therefore, all inducing conditions seem to lead to induction via titration of the GroE chaperonins by the increased level of nonnative proteins formed. Puromycin treatment failed to induce the ς(B)-dependent general stress regulon, indicating that nonnative proteins in general do not trigger this response. Reconstitution of HrcA-dependent heat shock regulation of B. subtilis in E. coli and complementation of E. coli groESL mutants by B. subtilis groESL indicate that the GroE chaperonin systems of the two bacterial species are functionally exchangeable.